An interesting co-existence of celiac disease and idiopathic pulmonary hemosiderosis: Lane Hamilton syndrome - Reis, Gökçe Pınar; Fettah, Ali; Volkan, Burcu; Özmen, Sevilay; Çalık, İlknur; Certel, Alev Cansu (The European Research Journal, 2019)
Idiopathic pulmonary hemosiderosis is characterized by hemoptysis resulting from recurring alveolar hemorrhage attacks, iron deficiency anemia, and parenchymal infiltrations as seen on chest radiographs. The clinical course may consist of silent and asymptomatic attacks, or it may sometimes exhibit a fulminant course with rapidly developing anemia and hypoxemia. Celiac disease is an autoimmune enteropathy triggered by the consumption of gluten-containing foods in genetically predisposed individuals. Co-existence of idiopathic pulmonary hemosiderosis and celiac disease is defined as Lane-Hamilton syndrome. We describe a case of Lane-Hamilton syndrome with growth and developmental delay; complete remission of pulmonary symptoms was achieved with a gluten-free diet.